Effect of Aqueous Administration of White Grub and Waste Extract on the Levels of Liver and Kidney Indices in Diabetic Rats: Effect of Aqueous Administration of White Grub and Waste Extract on the Levels of Liver and Kidney Indices in Diabetic Rats - Said, Said Sani (International Journal of Pharmaceutical & Biological Archive, 2020)
Introduction: The liver plays a major role in the regulation of carbohydrate metabolism, as it uses glucose as a fuel and kidneys are to excrete metabolic waste products as well as to maintain water, pH, electrolyte balance, production of calcitriol, and hemopoietin. Aim: This study aims to investigate the effect of the administration of white grub and waste on liver and kidney indices on diabetic rats. Materials and Methods: The rats were induced with diabetes by alloxanization and treated with the extracts of white grub and waste for 2 weeks. A total of 25 rats used, were randomly distributed into five groups (G1-G5) each with five rats. G1 served as normal control. G2-G5 served as diabetic control. At the end of the 1st week of extract administration, two animals from each group were randomly selected and sacrificed. At the end of the 2nd week, the remaining three animals from each group were also sacrificed and serum was collected for the determination of liver function indices (serum alkaline phosphatase [ALP], alanine aminotransferase [ALT], aspartate aminotransferase [AST] total bilirubin [TB], direct bilirubin [DB], total protein [TP], albumin [ALB], and globulin [GLB]) and kidney function parameters (urea, creatinine, and electrolyte [sodium â€œNa,â€ potassium â€œK,â€ bicarbonate â€œHCO3,â€ and chloride â€œClâ€]). Results: After the 1st week, the extract-treated group (G4 and G5) showed significant reductions of ALP, ALT, AST, TP, GLB, and ALB while TB and DB have normal value compared to diabetic untreated group and for renal function (G4 and G5) showed significantly lower levels of urea, Na, K, HCO3, creatinine, and Cl. After the 2nd week, the extract-treated group showed significant reductions of ALP, ALT, AST, DB, TP, ALB, and TB with significant increased levels of GLB and TP compared to diabetic untreated group (G2). G4 (extract treated) showed significantly (P < 0.05) lower levels of urea, Na, Cl, HCO3, and creatinine and with significant increased K levels compared to G2. G5 also extract-treated group indicates significant lower levels of urea, Cl, Na, and HCO3 and higher levels of creatinine and K compared to G2. Conclusion: These results suggest that the administration of aqueous extract of white grub and waste did not have any adverse effect on the liver and kidney functions in diabetic rats. The extracts have positive effect which showed that G4 (treated with whole white grub [WG]) is more effective compared to G5 (treated with WG waste).